Exploiting secondary raw materials from extractive waste facilities: A case study - Dino, Giovanna Antonella; Rossetti, Piergiorgio; Lorenzi, Alessio; Mister, Ivan; Cazzaniga, Alberto; Coulon, Frederic; Griffiths, Zoe; Wagland, Stuart T. (Unknown, 2018)
In recent years, resource scarcity has emphasised a need to transition from a linear to a circular flow of resources. Securing supplies of critical and secondary raw materials (CRM/SRM) for the manufacturing industry is at the forefront of industrial challenges, especially in Europe, USA and Asia. A key step towards achieving resource efficiency, is to recover these materials from anthropogenic waste deposits, such as urban landfill sites and extractive waste facilities. This means breaking away from the traditional linear use of resources to a closed-loop approach that allows maximum recovery of resources from waste. The management of extractive waste deposits and resource recovery is closely linked to the concept of urban mining. In this paper, we present a case study illustrating the feasibility of recovering SRM from EW facilities and discuss the pros and cons of undertaking such activities.